Merkel cell carcinoma of right buttock in an elderly patient: a case report (Medical Journal of Indonesia, 2015)
Merkel cell carcinoma is a rare primary cutaneous tumor. So far, few cases have been reported. Herewith we report a case of an 87-years-old male with painless, ulceroproliferative growth measuring 6x6 cm, over right upper outer quadrant of buttock; stage IIB (TNM, T3cNoMo). Patient received neo-adjuvant chemotherapy, injection of carboplatin 420 mg (day one) and etoposide 140 mg (day one to three) three weekly for three cycles followed external beam radiotherapy by Cobalt 60. At three months post-treatment follow-up, clinically no evidence of residual disease or recurrences noted. The purpose of reporting this case was to emphasize to its rarity, early asymptomatic clinical course leading to possibility of delayed diagnosis and paramount importance of high index of clinical suspicion in definitive diagnosis for better treatment result.